2017
DOI: 10.2147/ppa.s133222
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making for biologic treatment of autoimmune disease: influence on adherence, persistence, satisfaction, and health care costs

Abstract: Background Shared decision-making (SDM), a process whereby physicians and patients collaborate to select interventions, is not well understood for biologic treatment of autoimmune conditions. Methods This was a cross-sectional survey of adults initiating treatment for Crohn’s disease or ulcerative colitis (inflammatory bowel disease, IBD) or psoriatic arthritis or rheumatoid arthritis (RA/PA). Survey data were linked to administrative claims for 6 months before (baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 32 publications
1
70
0
2
Order By: Relevance
“…The studies varied in terms of methodology, data sources (eg database study vs single‐centre chart review), population (eg CD vs IBD; prior exposure to biologics), follow‐up time (exactly 6 months to a median of 22 months) and the definition of adherence. In six studies, adherence was measured by medication possession ratio (MPR), which is calculated by adding up the total days’ supply of a drug administered during a defined follow‐up period, which can be fixed (eg 365 days) or variable (start to end of therapy), and dividing by the total number of days in that period . Three studies adopted the commonly used adherence threshold MPR of ≥80% to define adherence, one study used a SAS macro programme to determine an optimal MPR threshold of ≥86% and two studies reported average MPR of the entire cohort .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies varied in terms of methodology, data sources (eg database study vs single‐centre chart review), population (eg CD vs IBD; prior exposure to biologics), follow‐up time (exactly 6 months to a median of 22 months) and the definition of adherence. In six studies, adherence was measured by medication possession ratio (MPR), which is calculated by adding up the total days’ supply of a drug administered during a defined follow‐up period, which can be fixed (eg 365 days) or variable (start to end of therapy), and dividing by the total number of days in that period . Three studies adopted the commonly used adherence threshold MPR of ≥80% to define adherence, one study used a SAS macro programme to determine an optimal MPR threshold of ≥86% and two studies reported average MPR of the entire cohort .…”
Section: Resultsmentioning
confidence: 99%
“…In the four studies that used an MPR threshold to define adherence, the overall proportion of adherent patients ranged from 38% to 77% (percentage of non‐adherent patients, 23%‐62%) . Among two studies reporting the average MPR of the entire patient cohort, adherence ranged from 89.7% to 97.4% …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, shared decisionmaking, as part of a successful treat-to-target approach [10,42], has been reported to improve patient satisfaction and adherence to medication in autoimmune diseases, allowing patients to achieve optimal management of their condition [48][49][50]. In addition, effective communication between a treating physician and a patient will enable the physician to promptly identify any potential AEs, ultimately leading to desirable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The case of Montgomery v Lanarkshire Health Board highlighted that patients need to be involved in their own care, in particular that they should have a say in their own treatment [7]; merely doing what professional's think is in the patient's best interest is not sufficient, the process of decision making has to be shared and the patient's own preferences established. SDM with patients who were initiating treatment for inflammatory bowel disease was shown to increase patient satisfaction, the likelihood of adherence to therapy, and a reduction in costs [8]. Reduction in prescribing [9], increased patient satisfaction [10] and greater patient confidence in decisions made [11,12] have all been reported.…”
Section: Introductionmentioning
confidence: 96%